User Model for Virtual Learning Based on Adaptive Gamification - Intan Yusrina Zairon; Tengku Siti Meriam Tengku Wook; Syahanim Mohd Salleh; Hadi Affendy Dahlan (IEEE Access)
This study presents the development and evaluation of a hybrid user model designed for adaptive gamification within a virtual learning environment based on the Felder-Silverman Learning Style model. The research aims to enhance student engagement and learning outcomes by personalizing gamification elements according to individual learning styles. The methodology consists of four phases: 1) analyzing learning styles among STEM students, 2) mapping gamification elements to their learning styles, 3) designing and developing a user model, and 4) evaluating its usability. The user model integrates both stereotypical and dynamic modeling approaches, allowing for initial categorization and continuous adaptation based on learner interactions. A cognitive walkthrough evaluation conducted with experts and end-users demonstrated high task completion rates, indicating the model’s potential effectiveness. Usability test results identified areas for improvement, specifically in visual design, navigation, and user feedback. The study contributes to the field of adaptive e-learning by providing a flexible framework that can potentially improve learning outcomes and sustain student engagement in virtual learning environments. Future work should focus on implementing the recommended enhancements and conducting empirical studies to validate the model’s effectiveness in real-world educational settings.